PENINJAUAN NIETODE PERHITUNGAN AWAL BULAN KAMARIAH KRITERIA MUHAMMADIYAH DENGAN KAJIAN ASTRONOMI - Arief Sasongko Adhi (Pusbindiklat - LIPI, 2009)
Muhammadiyah has long used a method which is based on the calculation of the conjunction of the Moon and the Sun to determine the beginning of Islamic months. If the conjunction happens before sunset and sunset happens before moonset, then the next day is the beginning of an Islamic month. Such a method often produces dates of the beginning of Islamic months which are earlier than the actual visibility of the lunar crescent. This research was conducted to compare the determination of the beginning ofIslamic months produced by different criteria. The criteria compared were Muhammadiyahs', Lapan's, SAAO's, and Odeh's. Astronomical data needed were obtained from Accurate Times 5.1 software for Cibinong area as the location of reference. Calculations were performed to determine the beginning of Islamic months starting from Sha'ban 1429 until Shawwal 1430. Comparison of the dates produced by the four criteria shows that those calculated by Muhammadiyah .'s criterion yielded in five differences out of 15 data points observed. It calls for a review on the criterion.